HLA-G 3’UTR Polymorphisms Are Linked to Susceptibility and Survival in Spanish Gastric Adenocarcinoma Patients - Vaquero-Yuste, Christian; Juarez, Ignacio; Molina-Alejandre, Marta; Molanes-López, Elisa María; López-Nares, Adrián; Suárez-Trujillo, Fabio; Gutiérrez-Calvo, Alberto; López-García, Adela; Lasa, Inmaculada; Gómez, Remedios; Fernández-Cruz, Eduardo; Rodrígez-Sainz, Carmen; et al. (Frontiers in Immunology, 2021)
HLA-G is a non-classical class I histocompatibility molecule that induces tolerance by acting on receptors of both innate and adaptive immune cells. When overexpressed in tumors, confers protection against the action of the immune system. The HLA-G gene shows several polymorphisms involved in mRNA stability, and, therefore, in the protein levels. We decided to study the implication of two polymorphisms (rs371194629; 14bp INS/DEL and rs1063320; +3142 C/G) in paired tissue samples (tumoral and non-tumoral) from 107 Spanish patients with gastric adenocarcinoma and 58 healthy control individuals, to assess the possible association of the HLA-G gene with gastric adenocarcinoma susceptibility, disease progression and survival. The presence of somatic mutations involving these polymorphisms was also analyzed. The frequency of the 14bp DEL allele was increased in patients (70.0%) compared to controls (57.0%, p=0.025). In addition, the haplotype formed by the combination of the 14bp DEL/+3142 C variants is also increased in patients (54.1% vs 44.4%, p=0.034, OR=1.74 CI95% 1.05-2.89). Kaplan-Meier analysis revealed that 14bp DEL/DEL patients showed lower 5-year life-expectancy than INS/DEL or INS/INS (p=0.041). Adjusting for TNM staging (Cox regression analysis) disclosed a significant difference in death risk (p=0.03) with an expected hazard 2.6 times higher. Finally, no somatic mutations were found when comparing these polymorphisms in tumoral vs non-tumoral tissues, which indicates that this is a preexisting condition in patients and not a de novo, tumor-restricted, event. In conclusion, the variants predominant in patients were those increasing HLA-G mRNA stability and HLA-G overexpression, clearly involving this molecule in gastric adenocarcinoma susceptibility, disease progression and survival and making it a potential target for immunotherapeutic approaches.